Budget deficits and inflation in thirteen Asian developing countries - Habibullah, Muzafar Shah; Chee, Kok Cheah; Abdul Hamid, Baharom (Center for Promoting Ideas, 2011)
In this study we attempt to determine the long-run relationship between budget deficit and inflation in thirteen Asian developing countries, namely; Indonesia, Malaysia, the Philippines, Myanmar, Singapore, Thailand, India, South Korea, Pakistan, Sri Lanka, Taiwan, Nepal and Bangladesh. Using annual data for the period 1950-1999 our Granger causality within the error-correction model (ECM) framework suggest that all variables involved (budget deficits, money supply and inflation) are integrated of order one. Our ECM model estimates indicate the existence of a long-run relationship between inflation and budget deficits. Thus, we conclude that budget deficits are inflationary in Asian developing countries.